205k views
5 votes
The expression 21 - (2x + 3)2 + 4 (1 - 1) + z3 can be simplified into the form

Ax3 + Bx2 +Cr + D. Find the missing constants A, B, C, and D below.

Show work please.

User Arafath
by
5.3k points

1 Answer

0 votes

Answer:

A=z

B=-2

C=0

D=30

Explanation:

First lets simply the equation

21 - (2x +3)2 + 4(1-1) + z^3

21 - (2x^2 + 9) + 4(0) + z ^3

21 - 2x^2 + 9 + z^3

- 2x^2 + z ^3 + 30

This means that:

A=z

B=-2

C=0

D=30

User Jerry Penner
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.